Kontribusi Sosial Muhammadiyah: Dari Teologi ke Aksi Nyata - Fathony, Bimba Valid; Permadi, Indra; Pambudi, Muhammad Sidiq (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Muhammadiyah, at its inception, was a religious organization that sought to provide answers to the problems faced by the community at that time. Al-Ma'un Theology is a concept initiated by KH. Ahmad Dahlan, the spirit of the Al-Ma'un letter became Muhammadiyah's support in carrying out social transformation as a form of implementing